PEMANFAATAN BELANJA ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DALAM PENCALONAN KEMBALI INCUMBENT - Yudha Satria, Romi; Fachruzzaman, Fachruzzaman; Robinson, Robinson (JURNAL FAIRNESS, 2013)
This study is aimed at investigating (1) whether differences exist in allocating the grant of ratio share and growth, society support, and financial support budgets within the incumbent local government budget before and during the process of regional election; (2) whether differences exist in allocating the grant, society support, and financial support budget during the regional election process between the incumbent and non incumbent candidates. This study uses census in which the data in this study is a secondary data obtained from the Election Commission of the Republic of Indonesia to determine the number of regions that have conducted the elections in 2011 and 2012, including incumbent and non-incumbent candidates. Object observed is grant expenditures, social assistance, and financial assistance in the budget fiscal year 2009-20112. Data analysis using descriptive statistics. The results of this study were (1) to prove empirically there is a difference ratio and the ratio of the proportion of growth allocated to regional grant expenditures incumbent before and during the election, (2) demonstrate empirically there are differences in the growth rate and the ratio of the proportion of grants allocated between local and regional nonincumbent incumbent upon election. With the increase in grant funding both the growth rate and the ratio of proportions, it should be assumed that the incumbent utilize Revenue and Expenditure (Budget) particularly in view of the re-nomination of grants for local office in the election.